Online Identity of Influencer @INIGANTA on Tiktok Social Media: Identitas Online Influencer @INIGANTA di Media Sosial Tiktok - Amanda, Awalia; Larasati, Cantika Aprilia (Universitas Muhammadiyah Sidoarjo, 2025)
Development of information and communication technology was changed the way individuals interact and build online identities in social media. The aims of this study to analyze the online identity of Aganta Ramadanu, known as @iniganta on TikTok, the context creator of the comedy content presented. The method qualitative approach with content analysis was used, which allows researchers to explore how Aganta builds a consistent and authentic self-image on the platform. The results showed that Aganta successfully managed the challenge of context collapse, where diverse audiences have different expectations, while still maintaining authenticity in the uploaded content. In addition, the research also identifies the risks and opportunities Aganta faces regarding privacy and participatory surveillance, and their impact on interactions with audiences. The findings provide insights into how online identities can be shaped and managed in the age of social media, as well as the importance of personal branding strategies in creating strong relationships with followers.